THE ANALYSIS OF STRUCTURAL RELIABILITY OF THE MAIN ELECTRIC CONNECTION CIRCUITS OF NUCLEAR POWER PLANTS - M. A. Korotkevich; A. L. Starzhinskij (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
The reliability of the main circuit of electrical connections at a nuclear electric power plant that has two units with a capacity of 1,200 MW each has been determined. Reliability, economical, maneuverable properties of the atomic power plant under study are largely determined by its main circuit, so the choice of the circuit for the design and its status in the process of operation occur to be critical objectives. Main electrical connection circuits in nuclear electric power plants are selected on the basis of the schematic networks of the energy system and the land attached to the plant. The circuit of the connection of a nuclear power plant to the grid in the original normal operating modes at all stages of the construction of such a plant should provide the outcome of the full added capacity of a nuclear power plant and the preservation of its stability in the power system without the influence of the emergency system automatics when any outgoing transmission line is disabled. When selecting the main circuit the individual capacity of the installed units and their number are taken into account as well as the order of development of the plant and power supply system; the voltage on which the power of a plant is delivered; a shortcircuit current for switchgear high voltage and the need for their limitation by circuit means; the most power that can be lost when damage to any switch. A model of reliability of the main circuit of electrical connections is designed to detect all types of accidents that are possible at the coincidence of failures of elements with the repair and operational modes that differs in composition and damageability of the equipment, as well as under conditions of the development of accidents due to failure of operation of devices of relay protection and automation.